A study of B→DK and D0 production using D0→K+pi-pi+pi- decays at LHCb - Hunt, P (2012)
A study of B(→)DK and D0 production using D0(→)K+pi-pi+pi- decays at LHCb A precision measurement of the CKM angle γ from tree-level processes is one of the principal goals of the LHCb experiment. Two important channels for the extraction of γ are B±→D0K± and B±→D̅ 0K±; a first study of these modes is presented using an integrated luminosity of Lint=35.6 ± 3.6pb−1 at a pp centre-of-mass collision energy of √—s=7TeV. A measurement is made of the ratio of branching fractions BDK/BDπ= Γ(B±→DK±)/Γ(B±→Dπ±)= 0.057 ± 0.007 ± 0.004 using B±→(K±π∓π±π∓)DK± and B±→(K±π∓π±π∓)Dπ± four-body D decay modes. This has an uncertainty competitive with the previous world average of (7.6 ± 0.6)%. A measurement is also made of the rate asymmetry between B−→(K−π+π−π+)DK− and B+→(K+π−π+π−)DK+ decays, Ac K3π fav =    Γ(B−→(K−π+π−π+)DK−)−Γ(B+→(K+π−π+π−)DK+)<hr noshade size=1>Γ(B−→(K−π+π−π+)DK−)+Γ(B+→(K+π−π+π−)DK+) <td nowrap>  = 0.01 ± 0.11 ± 0.06. As expected, this result is consistent with zero within statistical and systematic uncertainties. The D0/D̅ 0 production cross-section in bins oftransverse momentum and rapidity from prompt D0→K−π+π−π+ decays (and its charge conjugate) is presented, usingLint= 14.96 ± 0.52nb-1 of √—s=7TeV LHCb pp collision data. This measurement is important for testing predictions of QCD theoretical models, and determining LHCb's sensitivity to measurements of CPviolation, mixing measurements and rare decays of charmed hadrons. The results are compared to predictions from two different theoretical models and from the default LHCb tuning of the PYTHIA Monte Carlo event generator, and the results shown to be in good agreement. The cross-section results are also compared to an independent LHCb measurement in the D0→K−π+ decay channel. LHCb analyses rely on the ability to identify kaons and pions with a high efficiency and low mis-identification rate, achieved by two Ring Imaging Cherenkov (RICH) detectors. To ensure optimal performanceof the RICH detectors, the time alignment of the Level-0 (L0) front-end electronics modules has been optimised using a combination of a pulsed laser system installed in the LHCb cavern and pp collision data. After the time-alignment procedure, the L0 modules have been time-aligned to within approximately ±1ns across both detectors.